Evaluation of the Competitive Factors Affecting Ticket Prices in Low-Cost Airlines - YAŞAR, Mehmet (The Journal of Business Science, 2019)
Aim: This study was designed to determine the competitive elements that are thought to have an impact on the ticket prices of low-cost airlines.Method: Using ticket prices from routes in which Pegasus Airlines operates, a model was formed to examine the relationship between ticket prices and a variety of variables including the monthly frequency of the routes, the monthly available seats, the market share on the route, whether it is a monopoly on the route or not, the number of airlines operating on that route, whether there is another low-cost carrier on that route as well as the level of concentration on the route. Linear regression analysis and T-Test were used to test the model and reveal the levels of difference.Findings: The study found that market share, the number of flights on the route and route concentration values had a significant positive effect on the ticket prices. On the other hand, the presence of another low-cost airline on the route has a negative effect on ticket prices. In addition, ticket prices were found to be higher in monopoly markets and in markets with only one low-cost airline. Results: The research is important in terms of examining competitive effects on ticket prices.
Keywords: t-test; Ticket prices; Low Cost Carrier; Regression; T-Test; regresyon; Bilet Fiyatları; Düşük Maliyetli Taşıyıcı; Regresyon; T-Testi; low cost carrier; İşletme; t-testi; ticket prices; HG1-9999; bilet fiyatları; regression; düşük maliyetli taşıyıcı; Finance; Business Administration; 9. Industry and infrastructure; 1. No poverty; 12. Responsible consumption; 13. Climate action; 11. Sustainability; 8. Economic growth